2016
DOI: 10.1007/s00167-016-4109-y
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin clot prevents bone tunnel enlargement after ACL reconstruction with allograft

Abstract: Case-control study, Level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…10,11 Fibrin clots have been shown to enhance the surgical repair of tissue with poor healing capacity. [12][13][14] In 1988, Arnoczky et al 12 described the application of a fibrin clot to aid healing of meniscal defects in the avascular zone in a 1 canine model. Additional clinical studies have also shown increased healing of meniscal tears with the application of fibrin clots including complete radial tears in the avascular zone and horizontal cleavage tears.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10,11 Fibrin clots have been shown to enhance the surgical repair of tissue with poor healing capacity. [12][13][14] In 1988, Arnoczky et al 12 described the application of a fibrin clot to aid healing of meniscal defects in the avascular zone in a 1 canine model. Additional clinical studies have also shown increased healing of meniscal tears with the application of fibrin clots including complete radial tears in the avascular zone and horizontal cleavage tears.…”
mentioning
confidence: 99%
“…18 Furthermore, the addition of a fibrin clot to allograft in anterior cruciate ligament reconstruction has been shown to reduce the amount of tunnel widening at 1 year. 14 The use of platelet-rich plasma as a method to concentrate and deliver bioactive factors has been explored. 3 The platelets in platelet-rich plasma provide an increase in growth factors important for healing of compromised tissue.…”
mentioning
confidence: 99%
“…[8] The greater aperture widening was supported not only by a biomechanical study, but also by a clinical study. In a clinical study of 50 patients who underwent single-bundle ACL reconstruction with suspensory femoral fixation, Surer et al [9] showed that the tunnel widening was 0.3 to 10 mm greater in the aperture than in the midportion of the femoral tunnel regardless of using a fibrin clot. The main theory of the mechanism of the biological factor of tunnel widening was local inflammation to the localized cell necrosis of the ACL graft over time after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Surer et al divided the longitudinal axis of the bone tunnel into three equal portions. In each portion, the width of the tunnel was measured at the widest part 40 . This was done for the femoral and tibial tunnel on the AP radiograph and for the tibial tunnel only on the lateral radiograph, since the femoral tunnel is not easily identifiable on this view.…”
Section: Radiographsmentioning
confidence: 99%
“…This was done for the femoral and tibial tunnel on the AP radiograph and for the tibial tunnel only on the lateral radiograph, since the femoral tunnel is not easily identifiable on this view. The radiographs were taken immediately post-operatively, as well as at 1-year follow-up to calculate the amount of tunnel widening that had occurred 40 .…”
Section: Radiographsmentioning
confidence: 99%